The Connectivity of Nutrient Ratios on The Abundance of Phytoplankton Population In Jakarta Bay - Sidabutar Tumpak; Srimariana Endang S. (E3S Web of Conferences, 2020)
The frequency of algal bloom’s event has been increased in Jakarta Bay, recently. Most of the bloom events were tend to be reoccurred after the rainy season. The research was conducted from 2008 until 2015 to study the linkage of nutrients and the ratios on the growth of the phytoplankton population. Collecting samples were conducted using a canonical plankton net of 20 µm mesh size, 125 cm length and 30 cm diameter of the opening mouth. The results of the study showed that the concentration of phosphate in the waters ranged from 0.01-12.5 µg/l (average 4.58 µg/l) and nitrate ranged from 0.01-15.89 µg/l (average 0.72 µg/l). The N/P ratio during the study ranging from 0.2 up to 45.4. High ratios of nutrients were mostly recorded in 2010 where the overall abundance of phytoplankton is very high. There is a strong correlation of N/P ratio with the community structure or composition of the phytoplankton population. The variability of phytoplankton abundance appears to be related to nutrient ratios of nitrate and phosphate.